Peran “Warung Pesantrend” dalam Meningkatkan Kemandirian Ekonomi Santri: Tinjauan Ekonomi Syariah dan Ilmu Dakwah - Guspiati, Shopi; Hanif Fuadi, Muhamad (CV Kalimasada Group, 2024)
This study examines the role of “Warung Pesantrend” in the Miftahul Ulum Gandok Islamic Boarding School, Tasikmalaya City, in increasing the economic independence of students. The focus of the research is on student empowerment through pesantren economic activities, Fitofarmaka product development, and the integration of entrepreneurial learning with traditional pesantren education. Descriptive qualitative research methods are used with data collection techniques through observation, interviews, and documentation studies. The results of the study show that “Warung Pesantrend” plays a significant role in increasing the economic independence of students through direct involvement in business operations, product development, and marketing. The integration of sharia economic values and da'wah in student entrepreneurship activities also contributes to the formation of a resilient and ethical Muslim entrepreneurial character.